The influence of age at disease onset on disease activity and disability: results from the Ontario Best Practices Research Initiative. Issue 3 (March 2016) - Ruban, T.; Jacob, B.; Pope, J.; Keystone, E.; Bombardier, C.; Kuriya, B.
Abstract This study aims to compare characteristics between late-onset rheumatoid arthritis (RA) and young-onset RA and determine the association between age at disease onset and disease severity. We cross-sectionally studied 971 patients at the time of entry into the Ontario Best Practices Research Initiative, a registry of RA patients followed up in routine care. We restricted patients to ≤5 years of disease duration. Late-onset RA was defined as an onset ≥60 years of age and young-onset RA <60 years. Group differences were compared, and multivariate linear regression models were used to test the influence of age at onset on Disease Activity Score in 28 Joints with erythrocyte sedimentation rate (DAS28-ESR), Clinical Disease Activity Index (CDAI), and Health Assessment Questionnaire (HAQ) scores. The swollen joint count (6.2 vs. 5.3), acute phase reactants (C-reactive protein (CRP) 17.4 vs. 11.8 mg/L, ESR 30.6 vs. 21.5 mm/h), and comorbidity burden were higher in late-onset RA compared to young-onset RA (p < 0.01). Mean DAS28-ESR (4.6 vs. 4.3) and HAQ (1.2 vs. 1.1) scores were higher in late-onset RA patients (p < 0.05). Late-onset RA patients received more initial disease-modifying antirheumatic drug (DMARD) monotherapy and corticosteroids in comparison to greater DMARD/biologic combination therapy in young-onset RA patients (p < 0.05). Adjusted multivariate analyses showed that late-onset RA was independently associated with higher mean DAS28-ESR and HAQ scores, but not CDAI. Late-onset RA patients have greater disease activity that may contribute to disability early in the disease course. Despite this, initial treatment consists of less combination DMARD and biologic use in late-onset RA patients. This may have implications for future response to therapy and development of joint damage, disability, and comorbidities in this group.